The use of outdoor games and their effects on the body of schoolchildren - V.O. Kucher; I.M. Grygus (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Research purpose - to ground and define the role of outdoor games in physical education of children of midchildhood. 20 children of midchildhood, which were up-diffused on two identical groups (control and basic) on age and to physical development for 10 schoolchildren are involved in research. It is set that for the children of basic group the reaction of the respiratory system became better on the physical loading (on results the leadthrough of test of Serkin), the considerable improvement of function of breathing organs took a place. Set necessity of perfection of process of physical education of children. The measures of strengthening of interest are recommended to the lessons of physical culture for children, distributing and selection of games on the years of teaching. It is recommended in the process of teaching expressly to adhere to the following method of education of physical capabilities: complexity, regularity and sequence; duration of implementation of games and volume of loading; intervals of rest and their character.